Effects of bisphenol A on murine salivary glands and human tumor cell lines - Gabriela Kelly da Silva; José Alcides Almeida de Arruda; Tatiana Fernandes Araújo Almeida; Sicília Rezende Oliveira; Paula Alves da Silva Rocha; Ricardo Alves Mesquita; Zenilda de Lourdes Cardeal; Helvécio Costa Menezes; Ivana Márcia Alves Diniz; Soraia Macari; Andréia Machado Leopoldino; Tarcília Aparecida Silva (Experimental and Molecular Pathology, 2023)
Bisphenol A (BPA) is an endocrine-disrupting chemical with a potential role in endocrine cancers. However, the effects of BPA on the salivary glands have been barely explored. We investigated the impact of in vivo sub-chronic exposure to BPA and its in vitro effects on human salivary gland mucoepidermoid carcinoma cell lines. Male and female mice were exposed to BPA (30 mg/kg/day). Sublingual and submandibular salivary glands from an estrogen-deficiency model were also analyzed. BPA concentration in salivary glands was evaluated by gas chromatography coupled to ion trap mass spectrometry. Immunohistochemical analysis using anti-p63 and anti-α-SMA antibodies was performed on mouse salivary gland tissues. Gene expression of estrogen receptors alpha and beta, P63 and α-SMA was quantified in mouse salivary gland and/or mucoepidermoid (UM-HMC-1 and UM-HMC-3A) cell lines. Cell viability, p63 and Ki-67 immunostaining were evaluated in vitro. BPA disrupted the tissue architecture of the submandibular and sublingual glands, particularly in female mice, and increased the expression of estrogen receptors and p63, effects that were accompanied by significant BPA accumulation in these tissues. Conversely, ovariectomy slightly impacted BPA-induced morphological changes. In vitro, BPA did not affect the proliferation of neoplastic cells, but augmented the expression of p63 and estrogen receptors. The present data highlight a potential harmful effect of BPA on salivary gland tissues, particularly in female mice, and salivary gland tumor cells. Our findings suggest that estrogen-dependent pathways may orchestrate the effects of BPA in salivary glands.